2003
DOI: 10.1248/cpb.51.46
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Holothuroidea, 13. Structure of Neuritogenic Active Ganglioside Molecular Species from the Sea Cucumber Stichopus chloronotus.

Abstract: Three ganglioside molecular species, SCG-1, SCG-2, and SCG-3, were obtained from the lipid fraction of the chloroform-methanol extract of the sea cucumber Stichopus chloronotus. On the basis of chemical and spectroscopic evidence, the structures of these gangliosides have been determined to be 1 -2), and 1-O-[a a -L-fucopyranosyl-(1→11)-(N-glycolyl-a a -D-neuraminosyl)-(2→6)-b b-D-glucopyranosyl]-ceramide (SCG-3). The ceramide moieties were composed of heterogeneous long-chain base and fatty acid units. SCG-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
2

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] In the study of the GSLs of the sea cucumber Holothuria pervicax, we reported the isolation and structure of ten glucocerebrosides revealing a very close resemblance in structure.9) However, all these compounds still exist as a mixture of regio-isomers for terminal methyl groups in the side chain of the long-chain base (LCB) moiety, namely a mixture of iso and ante-iso isomers as shown in Fig. 1.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] In the study of the GSLs of the sea cucumber Holothuria pervicax, we reported the isolation and structure of ten glucocerebrosides revealing a very close resemblance in structure.9) However, all these compounds still exist as a mixture of regio-isomers for terminal methyl groups in the side chain of the long-chain base (LCB) moiety, namely a mixture of iso and ante-iso isomers as shown in Fig. 1.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Continuing the previous studies, three cerebroside molecular species (BAC-1, BAC-2 and BAC-3) was obtained from the less polar lipid fraction of CHCl 3 /MeOH extract of sea cucumber Bohadschia argus (Janomenamako in Japanese). The structures of BAC-1, BAC-2 and BAC-3 could be determined by hitherto reported chemical and spectroscopic methods 2,4,5) as the molecular species of typical types of glucocerebrosides, 2,4,5) namely, a sphingosine-type b-glucocerebroside possessing non-hydroxy fatty acid (BAC-1), a sphingosine-type b-glucocerebroside possessing 2-hydroxy fatty acid (BAC-2), and phytosphingosine-type b-glucocerebroside possessing 2-hydroxy fatty acid (BAC-3), respectively (data not shown), as revealed in Fig.…”
mentioning
confidence: 84%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] In the study of the GSLs of the sea cucumber Cucumaria echinata (gumi in Japanese), we reported the isolation and structure of glucocerebrosides 2,4) and monosialogangliosides.…”
mentioning
confidence: 99%